2011
DOI: 10.1021/es103729m
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Factors Affecting Sorption of Microcystins onto Natural Sediments

Abstract: The sorption of microcystins (MCs) to fifteen lake sediments and four clay minerals was studied as a function of sediment/clay properties, temperature, and pH through well−controlled batch sorption experiments. All sorption data for both sediments and clays are well described by a nonlinear Freundlich model (n f varies between 0.49 and 1.03). The sorption process for MCs exhibited different adsorptive mechanisms in different lake sediments mainly dependent on the sediment organic matter (OM). For sediments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
86
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(104 citation statements)
references
References 28 publications
16
86
1
1
Order By: Relevance
“…These findings suggest that the recovery of MCs was primarily affected by the type of sediments and MC variants, which agreed with the results reported by Babica et al [17]. The results of a previous study suggested that the sorption of MCRR, which has one more arginine residue than MCLR, can lead to the formation of cation bridges and more hydrogen bonds between MCs and the sediment surface [12]. This would explain why the extraction yields for MCRR were very lower than those for MCLR.…”
Section: Optimization Of the Solvent Extraction For Determination Of supporting
confidence: 91%
See 2 more Smart Citations
“…These findings suggest that the recovery of MCs was primarily affected by the type of sediments and MC variants, which agreed with the results reported by Babica et al [17]. The results of a previous study suggested that the sorption of MCRR, which has one more arginine residue than MCLR, can lead to the formation of cation bridges and more hydrogen bonds between MCs and the sediment surface [12]. This would explain why the extraction yields for MCRR were very lower than those for MCLR.…”
Section: Optimization Of the Solvent Extraction For Determination Of supporting
confidence: 91%
“…The increase in extraction efficiencies of MC with the decrease of the pH under acid conditions maybe resulted from: (1) the enhancement of the protonation of the two carboxylic acid groups in the MC molecules at lower pH (i.e., R-(COOH) 2 [29]) or (2) competition between the abundant H + and MCs for sorption sites on the sediment surface, and correspondingly, the tendency of the MCs to be extracted with less polar solvents such as methanol [17,28]. However, the recoveries of MCs from sediments extracted using 50% (v/v) methanol solutions under weakly acidic conditions were also much lower than those obtained under neutral conditions, which might have been caused by the strong adsorption of MCs in sediments under low pH solutions [12]. These findings suggest that a relatively higher recovery of MCs could only occur during the extraction of MCs in 50% (v/v) methanol solutions under neutral or very strong acid conditions.…”
Section: Optimization Of the Solvent Extraction For Determination Of mentioning
confidence: 97%
See 1 more Smart Citation
“…Numerous studies have reported that clay minerals effectively adsorb MCs through combining with their ionizable (carboxylic and/or amino) groups (Mohamed et al 2007; Morris et al 2000). Additionally, Wu et al (2011) found that sediment organic matters (SOMs) serve a dual function in adsorbing MCs. (i) SOMs inhibit MC sorption on organic-poor sediment (SOMs % <8 %) by competing for surface adsorption sites on sediment.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the dominant mechanism between MCLR molecule and sediment may be primarily attributed to hydrophilic interaction rather than hydrophobic binding. These discussions are based on a large amount of experimental data, where the sorption coefficient (K d ) of MCLR to sediments only ranged from several liters per kilogram to dozens of liters per kilogram (Wu et al 2011;Mohamed et al 2007).…”
Section: Introductionmentioning
confidence: 99%